Bone graft in the treatment of nonunion of the scaphoid with necrosis of the proximal pole: a literature review() - Severo, Antônio Lourenço (Rev Bras Ortop, 2017)
Scaphoid fractures are the most common fractures of the carpal bones, corresponding to 60%. Of these, 10% progress to nonunion; moreover, 3% can present necrosis of the proximal pole. There are various methods of treatment using vascularized and non-vascularized bone grafts. To evaluate and compare the rate of scaphoid consolidation with necrosis of the proximal pole using different surgical techniques. The authors conducted a review of the literature using the following databases: PubMed and BIREME/LILACS, where 13 case series were selected (ten with use of vascularized bone grafts and three of non-vascularized bone grafts), according to inclusion and exclusion criteria. In most cases VBGs were used, especially those based on the 1,2 intercompartmental supraretinacular artery, due to greater reproducibility in performing the surgical technique.